2013
DOI: 10.1021/cs300748g
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Reversal of Activities between Two Closely Related Heterogeneous Catalysts in the Aldol Reaction

Abstract: The relative rates of the aldol reaction catalyzed by supported primary and secondary amines can be inverted by 2 orders of magnitude, depending on the use of hexane or water as a solvent. Our analyses suggest that this dramatic shift in the catalytic behavior of the supported amines does not involve differences in reaction mechanism, but is caused by activation of imine to enamine equilibria and stabilization of iminium species. The effects of solvent polarity and acidity were found to be important to the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 43 publications
3
84
1
Order By: Relevance
“…However, the discovery rate may be further enhanced by exploiting more rational feedback obtained by means of kinetic modelling in the catalyst design cycle [3][4][5]. base amine sites has a enhancing effect on the catalytic activity of these amines in aldol condensations and other important C C coupling reactions [22][23][24][25][26][27][28][29][30][33][34][35][36][37][38]. Recently it has been demonstrated that an increasing acid strength of the promoting site leads to a decreasing activity which could be explained by a pronounced shift in the equilibrium from the free acid and free base towards the resulting neutralized ion pair [25,26,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, the discovery rate may be further enhanced by exploiting more rational feedback obtained by means of kinetic modelling in the catalyst design cycle [3][4][5]. base amine sites has a enhancing effect on the catalytic activity of these amines in aldol condensations and other important C C coupling reactions [22][23][24][25][26][27][28][29][30][33][34][35][36][37][38]. Recently it has been demonstrated that an increasing acid strength of the promoting site leads to a decreasing activity which could be explained by a pronounced shift in the equilibrium from the free acid and free base towards the resulting neutralized ion pair [25,26,32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the choice of solvent can impact the activity of the bifunctional catalyst. A recent report demonstrated that primary amines tethered to silica were more active for the aldol condensation of acetone and 4-nitrobenzaldehyde in water than in hexane because water shifted the equilibrium in favor of the aldol product and prevented the amine from forming an imine with 4-nitrobenzaldehyde, which inhibited the reaction [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effect of water in the aldol condensation have been previously reported elsewhere. 38,39 They have demonstrated the role of water in the regeneration of active basic group (amines) at the expense of the inactive iminium form. This kind of observation is unlikely in our case as we don't expect to have amines in our carbons based on our investigations.…”
Section: Figure 17 Ft-ir Of C-500 C-700 and C-900mentioning
confidence: 99%